Seroprevalence Study of Human Brucellosis by Conventional Tests and Indigenous Indirect Enzyme-Linked Immunosorbent Assay - Annapurna S. Agasthya; Srikrishna Isloor; Prabhudas Krishnamsetty (The Scientific World Journal)
Brucellosis is one of the most important reemerging zoonoses in many countries. Brucellosis is caused by Gram-negative coccobacillus belonging to genus Brucella. Human brucellosis often makes the diagnosis difficult. The symptoms and clinical signs most commonly reported are fever, fatigue, malaise, chills, sweats headaches, myalgia, arthralgia, and weight loss. Some cases have been presented with only joint pain, lower backache, and involuntary limb movement, burning feet, or ischemic heart attacks. The focus of this work was to develop a highly sensitive and specific indirect ELISA by using smooth lipopolysaccharide antigen of Brucella abortus 99 to detect anti-Brucella antibodies at Project Directorate on Animal Disease Monitoring and Surveillance. Serum samples collected from 652 individuals in whom fever was not the major symptom but the complaint was of joint pain, headache, lower backache, and so forth, were screened by Rose Bengal plate agglutination test (RBPT) and standard tube agglutination test (STAT). Subsequent testing of sera by indigenous indirect ELISA detected 20 samples positive (3.6% seroprevalence), and indirect ELISA was found to be more sensitive than RBPT and STAT. The seroprevalence in South Karnataka was 2.14%, and in North Karnataka it was 0.92%.